One-Pot Multicomponent Synthesis of 2H-Chromene Derivative, Kinetics, and Thermodynamic Studies Using a Stopped-Flow Technique in Combination with Theoretical Computation Methods. (26th May 2020) - Asheri, Osman; Shahraki, Mehdi; Habibi-Khorassani, Sayyed Mostafa
Abstract: The diethyl 6-bromo-2 H -chromene-2, 3-dicarboxylate (4 ) was successfully synthesized by the reaction between triphenylphosphine (1 ), diethyl acetylenedicarboxylate (DEAD, 2 ) and 5-bromo-2-hydroxybenzaldehyde acid (3 ) in the presence of dichloromethane. The 2H-chromene's compound were characterized using IR, 1 H, 13 C, and 31 P NMR spectroscopy. The kinetics and mechanism of the reaction were experimentally investigated by stopped-flow technique and UV–vis spectrophotometry. The first step in the proposed five-step mechanism, the reaction between 1 and 2 for the formation of intermediate 1 (I1 ), was fast. The reaction of I1 and 3 was slow and followed first-order kinetics. The experimental kinetic data proved that the step4 of the proposed mechanism is a rate-determining step. To make a further understanding about the proposed mechanism, theoretical investigations were carried out at the B3LYP/6-31++g(d, p) level of theory. The calculations showed that the step4 (Δ H 4 DEAD 0 = 82.1 kJ/mol) is in terms of energy undesirable and difficult in line with experimental results, and is an endothermic process. It also cleared that why I3 with diethyl groups in step4 tends to convert to the I4 very slowly through a four-member ring formation in comparison with other steps and ultimately it becomes impossible process (step4 ) when t -But groups are replaced instead of diethyl groups within the structure of I3 . The experimental and theoretical data indicated that the overall reaction rate follows second-order kinetics and depends on the concentrations of compounds 1 and 2 .